Differential Transcriptomes and Methylomes of Trophoblast Stem Cells From Naturally-Fertilized and Somatic Cell Nuclear-Transferred Embryos - Sun, Jin; Zheng, Weisheng; Liu, Wenqiang; Kou, Xiaochen; Zhao, Yanhong; Liang, Zehang; Wang, Lu; Zhang, Zihao; Xiao, Jing; Gao, Rui; Gao, Shaorong; Jiang, Cizhong (Frontiers in Cell and Developmental Biology, 2021)
Trophoblast stem cells (TSCs) are critical to mammalian embryogenesis by providing the cell source of the placenta. TSCs can be derived from trophoblast cells. However, the efficiency of TSC derivation from somatic cell nuclear transfer (NT) blastocysts is low. The regulatory mechanisms underlying transcription dynamics and epigenetic landscape remodeling during TSC derivation remain elusive. Here, we derived TSCs from the blastocysts by natural fertilization (NF), NT, and a histone deacetylase inhibitor Scriptaid-treated NT (SNT). Profiling of the transcriptomes across the stages of TSC derivation revealed that fibroblast growth factor 4 (FGF4) treatment resulted in many differentially expressed genes (DEGs) at outgrowth and initiated transcription program for TSC formation. We identified 75 transcription factors (TFs) that are continuously upregulated during NF TSC derivation, whose transcription profiles can infer the time course of NF not NT TSC derivation. Most DEGs in NT outgrowth are rescued in SNT outgrowth. The correct time course of SNT TSC derivation is inferred accordingly. Moreover, these TFs comprise an interaction network important to TSC stemness. Profiling of DNA methylation dynamics showed an extremely low level before FGF4 treatment and gradual increases afterward. FGF4 treatment results in a distinct DNA methylation remodeling process committed to TSC formation. We further identified 1,293 CpG islands (CGIs) whose DNA methylation difference is more than 0.25 during NF TSC derivation. The majority of these CGIs become highly methylated upon FGF4 treatment and remain in high levels. This may create a barrier for lineage commitment to restrict embryonic development, and ensure TSC formation. There exist hundreds of aberrantly methylated CGIs during NT TSC derivation, most of which are corrected during SNT TSC derivation. More than half of the aberrantly methylated CGIs before NT TSC formation are inherited from the donor genome. In contrast, the aberrantly methylated CGIs upon TSC formation are mainly from the highly methylated CGIs induced by FGF4 treatment. Functional annotation indicates that the aberrantly highly methylated CGIs play a role in repressing placenta development genes, etc., related to post-implantation development and maintaining TSC pluripotency. Collectively, our findings provide novel insights into the transcription dynamics, DNA methylation remodeling, and the role of FGF4 during TSC derivation.